Jewish renaissance in the Russian revolution - Moss, Kenneth B., 1974- (Harvard University Press, 2009)
Between 1917 and 1921, as revolution convulsed Russia, Jewish intellectuals and writers across the crumbling empire threw themselves into the pursuit of a 'Jewish renaissance'. Here, Kenneth Moss offers a comprehensive look at this movement.